Re-learning conflict in public space. Architecture as a provocation against urban inequality - Vera Cubas, Javier (2023)
The objective of this article is to show new possibilities of facing urban inequalities from the architectural point of view, in the current context of the city of Lima. Based on the hypothesis that inequality is a structural problem of Peruvian society, the attempts to confront it from the disciplines of architecture and urbanism ends up encouraging it, since the projects are elaborated from tools and methodologies disseminated by the same system that produces such inequalities. Based on a theoretical framework that criticizes the neoliberal urbanism, this paper analyzes a series of research-action projects (carried out in peripheral areas in Lima in the last five years, with the participation of the author) that propose urban regeneration based on recovering the public space, where architecture is used as a means to question socio-spatial dynamics and provoke positive conflicts that make possible the conquest of citizenship through the full exercise of the right to the city.